Highlands Community Green Map: our wilderness, arts, culture and sense of community... they're all breathtaking! - Highland District Community Association (Green Map System (Firm), 2009)
A map showing environmental and cultural points of interest in the area. Reverse of map features information about the region; First Nations' history; sections on climate, vegetation and wildlife; and background about the map project. First Nations artwork by John Elliot. Coordinator and editor Elaine Limbrick. Many community members contributed to this project, a number of them, along with sponsors and other contributors are named on the map itself. This map is part of the Green Map System.